2017
DOI: 10.1016/bs.enz.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Saliva-Exosomics in Cancer: Molecular Characterization of Cancer-Derived Exosomes in Saliva

Abstract: Exosomes are small membrane vesicles of endocytic origin that are secreted by most cells and detected in saliva. Pathophysiological roles for salivary exosomes are beginning to be recognized in diseases including cancer, highlighting potential biomarkers and biological functions. Since early detection of cancer is vital for successful treatment, salivary exosomes would be advantageous in achieving a better survival rate due to their ready availability and noninvasiveness. The use of salivary exosomes may there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 149 publications
(175 reference statements)
3
82
0
3
Order By: Relevance
“…One of the bottlenecks in the clinical application of EVs as drug carriers is that there is no uniform standard for the separation of EVs (Li et al, 2017;Merchant et al, 2017). EVs are widely found in blood (Ruivo et al, 2017), saliva (Nonaka & Wong, 2017), urine (Street et al, 2017), and other biological fluids as carriers of cellular information (Ferguson & Nguyen, 2016). Effective extraction and separation of these EVs from different sources for the purpose of drug delivery remain challenging (Nonaka & Wong, 2017;Street et al, 2017).…”
Section: Lack Of Standardized Isolation and Purification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the bottlenecks in the clinical application of EVs as drug carriers is that there is no uniform standard for the separation of EVs (Li et al, 2017;Merchant et al, 2017). EVs are widely found in blood (Ruivo et al, 2017), saliva (Nonaka & Wong, 2017), urine (Street et al, 2017), and other biological fluids as carriers of cellular information (Ferguson & Nguyen, 2016). Effective extraction and separation of these EVs from different sources for the purpose of drug delivery remain challenging (Nonaka & Wong, 2017;Street et al, 2017).…”
Section: Lack Of Standardized Isolation and Purification Methodsmentioning
confidence: 99%
“…EVs are widely found in blood (Ruivo et al, 2017), saliva (Nonaka & Wong, 2017), urine (Street et al, 2017), and other biological fluids as carriers of cellular information (Ferguson & Nguyen, 2016). Effective extraction and separation of these EVs from different sources for the purpose of drug delivery remain challenging (Nonaka & Wong, 2017;Street et al, 2017). Hitherto, five separation methods have been developed for isolation of EVs: (1) ultracentrifugation-based isolation techniques;…”
Section: Lack Of Standardized Isolation and Purification Methodsmentioning
confidence: 99%
“…Exosomes isolated from glandular saliva were shown to possess miRNAs unique to salivary gland disease status (Michael et al, 2010). The use of salivary exosomes as biomarkers for cancer has been recently reviewed (Nonaka and Wong, 2017). Characterization of intact exosomes by FTIR distinguished exosomes of Oral Cancer subjects from Healthy individuals and suggests a noninvasive method for future diagnosis of oral cancer in early stages (Zlotogorski-Hurvitz et al, 2019).…”
Section: Exosome Role In Oral and Systemic Disease Diagnosismentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) is an alternative and/or complimentary analytical method of great potential for the detection and analysis of biomarkers that are present in saliva, at the atomic level. Probing and characterization at the atomic level is of high importance for salivaomics, as it was recently observed that information in saliva is not only found in locally-produced molecules, but also carried from distant tissues through nano-vesicles [18]. NMR, as a powerful analytical method, can identify and quantitively analyze organic acids, amino acids, fatty acids, amines, and alcohol in the provided biofluid sample.…”
Section: The Role Of Nuclear Magnetic Resonance In Saliva Testing Andmentioning
confidence: 99%